Consumer preferences expressed via shopping in alternative food chains - Miškolci, Simona (Mendelova univerzita v Brně, 2017)
In recent years an increasing consumer interest in shopping in alternative food chains can be observed also in the Czech Republic. For the successful development of alternative food networks, it is important to understand what motivates consumers to shop there. This paper is aimed to define and discuss the key aspects of the preference determinants of AFN shoppers. The empirical analysis was conducted on 333 shoppers at two alternative food chains in Brno, Czech Republic. The consumer survey was designed to examine cognitive, normative and affective determinants of preference for purchased food. First findings confirm, that by the shopping at alternative food chains consumers demonstrate preferences not only for fresh and tasty food, but also their normative position of willingness to support local production and community.

V posledních letech lze pozorovat rostoucí zájem spotřebitelů o nákup v alternativních potravinových řetězcích i v České republice. Pro úspěšný rozvoj alternativních potravinových sítí je důležité pochopit, co motivuje spotřebitele k nákupu. Článek je zaměřen na vymezení a diskusi klíčových aspektů determinujících preference nakupujících v alternativních potravinových sítích. Empirický průzkum názorů spotřebitelů byl proveden u 333 zákazníků ve dvou alternativních potravinářských řetězcích v Brně. Spotřebitelský průzkum byl navržen tak, aby zkoumal kognitivní, normativní a afektivní determinanty preferencí pro nákup potravin. První zjištění potvrzují, že nákupem v alternativních potravinových řetězcích spotřebitelé projevují preference nejen pro čerstvé a chutné potraviny, ale i své normativní postoje ochoty podpořit místní produkci a komunitu.
Spotřebitelské preference vyjádřené prostřednictvím nákupu v alternativních potravinových řetězcích
Keywords: Alternative food chains; Credence characteristics; Customer motives; Preference determinants; Alternativní potravinové řetězce; vnitřní charakteristiky; spotřebitelské motivy; determinanty preferencí